Revisiting the causes of organizational discontinuance: A diffusion theory approach offers new insights - Madhavan Parthasarathy; David Forlani (jbm - Journal of Business Market Management, 2016)
The purpose of this research was to develop a framework capable of classifying the reasons behind the discontinuance of supplier-distributor relationships. Using a sample of CEO's who manage intra-national and multi-national firms, a study was run to test a typology of discontinuance built around diffusion theory's source of influence construct (e.g., the origin and valence of the information that initiates a discontinuance decision). The three types are called New Day, Strike 3 and Greener Grass. Results support the proposed typology and suggest that managers indeed terminate relationships with partner firms for three aforementioned theoreticallygrounded and practitioner-relevant reasons. Managers can use the framework to better understand their past and current relationships, as well as a tool for engineering future relationships. Finding a tendency toward one discontinuance type can help managers identify issues or weaknesses that if addressed, could improve the quality and longevity of such relationships.
urn:nbn:de:0114-jbm-v9i2.1379
Keywords: 650; Organizational discontinuance; Channel relationships; Diffusion theory